Gut microbiota differently contributes to intestinal immune phenotype and systemic autoimmune progression in female and male lupus-prone mice. Issue 108 (March 2020) - Johnson, Benjamin M.; Gaudreau, Marie-Claude; Gudi, Radhika; Brown, Robert; Gilkeson, Gary; Vasu, Chenthamarakshan
Abstract: The risk of developing systemic lupus erythematosus (SLE) is about 9 times higher in women as compared to men. Our recent report, which used (SWRxNZB) F1 (SNF1) mouse model of spontaneous lupus, showed a potential link between immune response initiated in the gut mucosa at juvenile age (sex hormone independent) and SLE susceptibility. Here, using this mouse model, we show that gut microbiota contributes differently to pro-inflammatory immune response in the intestine and autoimmune progression in lupus-prone males and females. We found that gut microbiota composition in male and female littermates are significantly different only at adult ages. However, depletion of gut microbes causes suppression of autoimmune progression only in females. In agreement, microbiota depletion suppressed the pro-inflammatory cytokine response of gut mucosa in juvenile and adult females. Nevertheless, microbiota from females and males showed, upon cross-transfer, contrasting abilities to modulate disease progression. Furthermore, orchidectomy (castration) not only caused changes in the composition of gut microbiota, but also a modest acceleration of autoimmune progression. Overall, our work shows that microbiota-dependent pro-inflammatory immune response in the gut mucosa of females initiated at juvenile ages and androgen-dependent protection of males contribute to gender differences in the intestinal immune phenotype and systemic autoimmune progression. Highlights: Intestine of juvenile female lupus-prone SNF1 (SWRxNZB) F1 (SNF1) mice expresses higher pro-inflammatory cytokines. Gender specific difference in gut microbiota appears only at adult age. Depletion of gut microbiota modulates autoimmune progression in females, but not in males. Microbiota transfer studies suggest gut microbes from males and females are functionally different in modulating systemic autoimmunity. Orchidectomy alters gut microbiota composition and causes modest acceleration of autoimmune progression in males.